A randomized controlled comparative study of efficacy of oral metronidazole versus oral tinidazole in amebic liver abscess - Kumar, Vivek; Kumar, Deepak; Kumar, Devunoori Arun; Mukul; Tiwari, Shivam; Sadhyan, Saksham (International Surgery Journal, 2025)
Background: Amebic liver abscess (ALA), a significant complication of amebiasis, is commonly treated with anti-amebic drugs like metronidazole and tinidazole. This randomized controlled study aimed to compare the efficacy and safety of oral metronidazole and tinidazole in treating ALA. Methods: Sixty patients with radiologically confirmed right lobe ALA were randomized into two groups: Group A received metronidazole (30-40 mg/kg/day in three divided doses), and Group B received tinidazole (50 mg/kg/day in divided doses). Baseline demographic, clinical, and laboratory parameters were comparable between the groups. Primary outcomes included the time to 50% reduction in pain and fever resolution, while secondary outcomes assessed drug tolerability, the need for additional antibiotics, and abscess drainage. Results: Both groups demonstrated significant symptom resolution over 96 hours, with comparable reductions in pain (assessed by the Visual Analog Scale) and fever. None of the patients required abscess drainage or experienced complications during the study period. Tinidazole showed similar efficacy to metronidazole, with slightly better tolerability. Both drugs achieved significant clinical and radiological improvements, and there were no statistically significant differences in outcomes between the two groups. Conclusions: This study confirms that both metronidazole and tinidazole are effective and safe for treating uncomplicated ALA. Tinidazole, with its prolonged bioavailability and fewer side effects, is a viable alternative to metronidazole.